atTic110 Functions as a Scaffold for Coordinating the Stromal Events of Protein Import into Chloroplasts - Inaba, Takehito; Li, Ming; Alvarez-Huerta, Mayte; Kessler, Félix; Schnell, Danny J. (My University, 2003)
The translocon of the inner envelope membrane of chloroplasts (Tic) mediates the late events in the translocation of nucleus-encoded preproteins into chloroplasts. Tic110 is a major integral membrane component of active Tic complexes and has been proposed to function as a docking site for translocation-associated stromal factors and as a component of the protein-conducting channel. To investigate the various proposed functions of Tic110, we have investigated the structure, topology, and activities of a 97.5-kDa fragment of Arabidopsis Tic110 (atTic110) lacking only the amino-terminal transmembrane segments. The protein was expressed both in Escherichia coli and Arabidopsis as a stable, soluble protein with a high α-helical content. Binding studies demonstrate that a region of the atTic110-soluble domain selectively associates with chloroplast preproteins at the late stages of membrane translocation. These data support the hypothesis that the bulk of Tic110 extends into the chloroplast stroma and suggest that the domain forms a docking site for preproteins as they emerge from the Tic translocon.